2012
DOI: 10.3758/s13415-012-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Positive emotion broadens attention focus through decreased position-specific spatial encoding in early visual cortex: Evidence from ERPs

Abstract: Recent evidence has suggested that not only stimulus-specific attributes or top-down expectations can modulate attention selection processes, but also the actual mood state of the participant. In this study, we tested the prediction that the induction of positive mood can dynamically influence attention allocation and, in turn, modulate early stimulus sensory processing in primary visual cortex (V1). High-density visual event-related potentials (ERPs) were recorded while participants performed a demanding task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 98 publications
(165 reference statements)
5
77
1
Order By: Relevance
“…Thus, when attentional resources are spread over a larger portion of the visual field, this gain in spatial attention is somehow counteracted by a loss regarding the processing of the details and local information. In line with this prediction, we found in our previous study (Vanlessen, et al, 2013) that participants in the positive mood group showed a drop in accuracy for processing the content (i.e., local elements) of these textures shown in the upper visual field, compared to the participants in the neutral mood group.…”
Section: Costs and Benefits Of A Broadening Of Attention Under Positisupporting
confidence: 60%
See 3 more Smart Citations
“…Thus, when attentional resources are spread over a larger portion of the visual field, this gain in spatial attention is somehow counteracted by a loss regarding the processing of the details and local information. In line with this prediction, we found in our previous study (Vanlessen, et al, 2013) that participants in the positive mood group showed a drop in accuracy for processing the content (i.e., local elements) of these textures shown in the upper visual field, compared to the participants in the neutral mood group.…”
Section: Costs and Benefits Of A Broadening Of Attention Under Positisupporting
confidence: 60%
“…However, this behavioral effect was evidenced only in a control experiment where no EEG was recorded concurrently (Vanlessen, et al, 2013). Hence, we could link these behavioral effects with the changes observed at the level of the C1 only indirectly.…”
Section: Costs and Benefits Of A Broadening Of Attention Under Positimentioning
confidence: 99%
See 2 more Smart Citations
“…positive emotion has been associated with a broadening of spatial attention and increased susceptibility to peripheral stimuli and distractors (Basso, et al, 1996;Gasper & Clore, 2002;Jefferies, et al, 2008;Vanlessen, Rossi, De Raedt, & Pourtois, 2013). The ventral parietal regions that are reported here to be modulated by mood valence have previously been linked with bottom-up attentional processes during memory tasks (Cabeza, et al, 2008;Ciaramelli, et al, 2010), whereby attention is automatically captured by old stimuli, leading to retrieval of those items from memory.…”
Section: Discussionmentioning
confidence: 83%